Stimulus type and social context are stronger than individual differences in common marmosets' novelty exploration - Brügger, Rahel K.; Gokcekus, Samin; Burkart, Judith M.; Forss, Sofia I.F. (Animal behaviour, 2025)
Consistent individual differences in animals' reactions to novel objects and foods serve as a proximate measure of personality in many subfields of biology and psychology. However, these responses may be subject to contextual influences such as the nature of the novel stimuli and the social context during the tests. To help gain some more clarity as to whether this widely used method provides a robust measure of personality, here, we focus on the exploration axis of personality. How animals explore novel objects has important implications for how they innovate, learn from and interact in the environment. We therefore evaluate the robustness of exploration tendency within and across contexts as well as time by testing common marmosets, Callithrix jacchus, with a ‘test battery’ of 12 novel stimuli from 2 categories (food and objects) in both individual and social contexts. Furthermore, we compare the stability of individual exploration tendency over a period of 2 years in two similar novelty exploration tests. We find that marmosets' reactions measured in terms of latency to touch items, number of exploration events and proportion of exploration time are predominantly explained by the stimulus category and the social context. We do not find strong support for consistent individual differences. Moreover, we observe no correlation between responses in the novelty exploration tests conducted 2 years apart. Our results show that social context and stimulus type can lead to differences in exploration tendency and thereby emphasize the importance of considering these variables, when using novel stimulus paradigms, which apply to a broad range of scientific disciplines such as animal cognition, behavioural ecology and comparative psychology. •Marmosets' exploration tendency is influenced by stimulus type and social context.•Food and object neophobia are likely distinct processes.•We lack strong support for consistent individual differences in exploration.•Individuals' novelty exploration assessed 2 years apart is not correlated.